Mechanical Behaviour of Engineering Materials Metals, Ceramics, Polymers, and Composites - Roesler, Joachim. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
How do engineering materials deform when bearing mechanical loads? To answer this crucial question, the book bridges the gap between continuum mechanics and materials science. The different kinds of material deformation (elasticity, plasticity, fracture, creep, fatigue) are explained in detail. The book also discusses the physical processes occurring during the deformation of all classes of engineering materials (metals, ceramics, polymers, and composites) and shows how these materials can be strengthened to meet the design requirements. It provides the knowledge needed in selecting the appropriate engineering material for a certain design problem. The reader will thus learn how to critically employ design rules and thus to avoid failure of mechanical components. ‘Mechanical Behaviour of Engineering Materials’ is both a valuable textbook and a useful reference for graduate students and practising engineers.